Helical twisting power of antiferroelectric chiral terphenyls in different matrices. (2nd November 2018) - Tykarska, Marzena; Kurp, Katarzyna; Pietrzak, Grzegorz; Czerwiński, Michał
ABSTRACT: To determine the influence of chemical structure on the Helical Twisting Power (HTP), we tested four optically active dopants having a terphenyl rigid core and the same chiral centre but differing in the length of nonchiral terminal chain and the substitution of benzene rings with fluorine atoms. The compounds were added to different achiral liquid crystalline matrices: nematic and smectic C. It was found that HTP as well as its temperature variation depends on the kind of used matrices. It gives a conclusion that information about HTP obtained in one matrix cannot be uncritically transferred to another one.